Flow Cytometry as a Rapid and Valuable Method in Investigation of Colistin Resistance in Carbapenem-Resistant Klebsiella pneumoniae Isolates - Şafak Ceren Uçak; Betigül Öngen (MDPI AG, 2024)
Rapid detection of antimicrobial resistance is crucial for early initiation of appropriate therapy. The aim of this study was to investigate whether resistance to colistin, the last-resort antibiotic, in carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates can be detected accurately and rapidly by flow cytometry (FCM). The VITEK 2 automated system was used to identify 85 K. pneumoniae strains and to determine their resistance to carbapenems. The minimum inhibitory concentration (MIC) values for colistin in 85 CRKP strains were determined by broth microdilution (BMD), which is the reference method. In addition, FCM was used, combined with DiBAC4(3) fluorescent stain, to determine colistin susceptibility. The MIC₅₀ value of the strains, 80% of which were resistant to colistin by the BMD method, was 16 mg/L, and the MIC₉₀ value was 32 mg/L. When FCM was compared with the reference method, it was determined that the specificity was 94.1%, sensitivity was 100% of FCM, and Cohen's kappa value was 0.96. Colistin susceptibility results with FCM were obtained within an average of 2 h. These findings suggest that FCM holds great promise as a rapid and reliable alternative method for detecting colistin resistance in CRKP strains.